2008
DOI: 10.1007/s00299-008-0607-9
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively activated barley ROPs modulate epidermal cell size, defense reactions and interactions with fungal leaf pathogens

Abstract: RHO-like monomeric G-proteins of plants (ROPs, also called RACs), are involved in plant development and interaction with the environment. The barley (Hordeum vulgare) ROP protein HvRACB has been shown to be required for entry of the biotrophic powdery mildew fungus Blumeria graminis f.sp. hordei (Bgh) into living host cells. To get a deeper insight into evolutionarily conserved functions of ROPs in cell polarity and pathogen responses, we stably expressed constitutively activated (CA) mutant variants of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 55 publications
4
66
0
1
Order By: Relevance
“…Generally, the shape of epidermal cells was less regular in CA HvRAC/ROP barley. 3 We also observed the presence of more than one short epidermal cell in between two stomata (Fig. 1B) or two stomata lacking an intercalated short epidermal cell (Fig.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Generally, the shape of epidermal cells was less regular in CA HvRAC/ROP barley. 3 We also observed the presence of more than one short epidermal cell in between two stomata (Fig. 1B) or two stomata lacking an intercalated short epidermal cell (Fig.…”
mentioning
confidence: 85%
“…RAC/ROP GTPases play regulatory roles in polar growth and cell morphogenesis in several cell systems including pollen tubes, developing root hairs and leaf pavement cells. 2 In a recent publication, 3 we showed that constitutively activated (CA) mutants of different barley (Hordeum vulgare) RAC/ROPs support susceptibility to the barley powdery mildew fungus Blumeria graminis f.sp. hordei (Bgh).…”
mentioning
confidence: 99%
“…Based on phylogenetic analysis AtRLCK VI_A3 might be the ortholog of the barley RLCK HvRBK1, which interacts with the powdery mildew susceptibility factor HvRACB in yeast and in planta (Huesmann et al 2012). there is evidence that RAC/ROP activity in Arabidopsis and barley contributes to susceptibility to powdery mildew fungi (Dörmann et al 2014;Hoefle et al 2011;Huesmann et al 2011;Pathuri et al 2008;Poraty-Gavra et al 2013). Recently, it was shown that DN AtROP6, restricted reproductive success of the powdery mildew fungus Golovinomyces orontii on Arabidopsis, perhaps suggesting a function of wild type AtROP6 in susceptibility (Poraty-Gavra et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…18 Depolarization of normally tip-growing root hairs also takes place when a constitutively activated (CA) version of barley HvRACB is stably expressed in barley. 12 The same CA HvRACB plants are super-susceptible to powdery mildew. However, super-susceptible Atropgap1 or Atropgap4 mutants do not display aberrant root hairs, suggesting function of other ROPGAPs in root hair growth (data not shown).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…6,7 In barley, HvRACB was identified as susceptibility factor to penetration by Blumeria graminis f.sp hordei (Bgh), influencing actin reorganization during pathogen attack. [8][9][10][11][12] Stable knock-down of HvRACB expression inhibits penetration success of Bgh and impairs establishment and expansion of fungal haustoria in barley epidermal cells. Furthermore, HvRACB is required for initiation and elongation of barley root hairs and affects adult plant height similar the barley roP GtPase hvraCB is a susceptibility factor of barley to powdery mildew caused by the biotrophic fungus Blumeria graminis f.sp hordei (Bgh).…”
mentioning
confidence: 99%